ANALYSIS OF THE IMPACT OF TECHNOLOGY IN DIGITAL ENTREPRENEURSHIP DEVELOPMENT - Rachmat Taufik (Jurnal Scientia, 2023)
This research aims to analyze the impact of technology in the development of digital entrepreneurship. Digital entrepreneurship has become increasingly important in today's digital era, where information and communications technology (ICT) has changed the way businesses operate. This research uses a qualitative approach with descriptive methods where in this research, we collect data from various sources, including digital entrepreneurs, industry stakeholders, and related literature. The results of this research reveal that in the era of industrial revolution 4.0, digital entrepreneurship has become the key to success in business. The ability to utilize technology, analyze data, and collaborate with various platforms and partners is a crucial factor in achieving sustainable business growth. Digital business people need to develop special skills in reaching customers online, designing products and services, managing data, and implementing digital marketing strategies effectively. In addition, technology also enables reduced operational costs, increased revenue, and the ability to adapt businesses quickly to market changes. Thus, technology is the main driver in the development of digital entrepreneurship, opening up great opportunities for business growth and innovation in this digital era.